Inheritance sf resistance to yellow vein mosaic virus in an interspecific cross of okra (Abelmoschus esculentus) - Dhankhar, S K; Dhankar, B S; Yadava, R K (The Indian Journal of Agricultural Sciences, 2005)
The nature of inheritance for resistance to yellow vein mosaic virus of okra [Abelmoschus esculentus (L.) Moench] in an interspecific cross of ’Hisar Unnat’ Abelmoschus esculentus x Abelmoschus manihot (L.) Medikus ssp manihot was investigated at Hisar, Haryana, during rainy seasons of 1999-2003 under highly efficient natural epiphytotic conditions. The cross-compatibility was one way, ie when ’Hisar Unnat’ A. esculentus was used as a female parent. The F1 fruits were generally seedless, however, backcrosses could be attempted with partial success. The resistance showed Mendelian segregation as per the condition governed by 2 complimentary dominant genes.